INFLUENCE OF INDIVIDUAL, ENVIRONMENT, AND MOTIVATION FACTORS OF ATTENDING PHYSICIANS (DPJPs) ON PATIENT ROUND TIMELINESS AT DR. SAIFUL ANWAR REGIONAL HOSPITAL EAST JAVA PROVINCE ON THE PUNCTUALITY OF VISITES AT DR. SAIFUL ANWAR HOSPITAL, EAST JAVA PROVINCE - Pratiwi, Suryanti Dwi; Holipah, Holipah; Rahmah, Shofi Nur (Universitas Brawijaya, 2025)
The timeliness of patient rounds by Attending Physicians (DPJPs) in hospitals significantly impacts various aspects of healthcare delivery, such as patient waiting times, treatment efficiency, and discharge processes. At Dr. Saiful Anwar Hospital, the level of compliance with punctual patient round standards remains below the national benchmark, which is recorded at 68.83%. This study aimed to analyze the influence of individual, environment, and motivation factors on the timeliness of rounds conducted by DPJPs at Dr. Saiful Anwar Regional Hospital, East Java Province. A quantitative, cross-sectional research design was used by involving 240 respondents selected through consecutive sampling. Data were collected using a questionnaire and analyzed using multiple linear regression. The results indicated that individual factors (gender, age, length of employment, and employment status), environment factors (access routes and medical facilities), and motivational factors (income, hospital policies, time pressure, and co-worker support) had no significant effect on patient round timeliness. This study found that timeliness was more influenced by adherence to professional ethics and a commitment to patient care, indicating that DPJPs continue to prioritize service quality despite operational challenges. In conclusion, external conditions and personal characteristics do not appear to be the primary determinants of timely rounds. To enhance service efficiency, hospitals are encouraged to optimize internal systems, such as scheduling, interprofessional coordination, and operational policy evaluation, to better support the timely execution of DPJP responsibilities.